Telomeres susceptibility to environmental arsenic exposure: Shortening or lengthening? - Wai, Kyi Mar; Swe, Thinzar; Myar, Maw Thoe; Aisyah, Cindy Rahman; Hninn, Thae Su Su (Frontiers in Public Health, 2023)
Maintaining telomere length plays a crucial role in regulating cellular life span. Telomere lengthening or shortening is one of the important biomarkers which could predict the preceding or present diseases. Meanwhile, the impact of environmental arsenic exposure on telomere length has increasingly concerned. Although previous studies demonstrated the effects of arsenic on telomere length, the findings were unclear on whether telomere shortens or lengthens by arsenic exposure. Thus, this manuscript summarized and discussed the telomere length alteration following arsenic exposure and the possible does-response effect of arsenic on telomere length. The present review suggested that different age groups may respond differently to arsenic exposure, and the dose-response effect of arsenic could be a critical factor in its effect on telomere length. Moreover, speciation analysis of arsenic could be more informative in identifying the effect of arsenic on telomere length.